Economic efficiency of industrial introduction of a torsion and percussive cultivator of soil - Бабицький, Л. Ф.; Падалка, В. В.; Ляшенко, С. В. (Scientific Progress & Innovations, 2012)
The necessity of use of active soil cultivators for improvement of physical and mechanical properties of farm lands has been proved. Results of calculation of economic efficiency of use of a torsion and percussive soil cultivator have been presented. Economic efficiency of use of torsion and percussive soil cultivator has been confirmed. The economy of fuel has been experimentally confirmed in the technological process of non-turnaround soil tilling by the unit in structure MTZ-80 + a torsion and percussive soil cultivator in comparison with a known prototype.